Highly sensitive detection of the PIK3CAH1047R mutation in colorectal cancer using a novel PCR-RFLP method. Issue 1 (December 2016) - Li, Wan-Ming; Hu, Ting-Ting; Zhou, Lin-Lin; Feng, Yi-Ming; Wang, Yun-Yi; Fang, Jin
Abstract Background ThePIK3CA H1047R mutation is considered to be a potential predictive biomarker for EGFR-targeted therapies. In this study, we developed a novel PCR-PFLP approach to detect thePIK3CA H1047R mutation in high effectiveness. Methods A 126-bp fragment ofPIK3CA exon-20 was amplified by PCR, digested with FspI restriction endonuclease and separated by 3 % agarose gel electrophoresis for the PCR-RFLP analysis. The mutant sequence of thePIK3CA H1047R was spiked into the corresponding wild-type sequence in decreasing ratios for sensitivity analysis. Eight-six cases of formalin-fixed paraffin-embedded colorectal cancer (CRC) specimens were subjected to PCR-RFLP to evaluate the applicability of the method. Results The PCR-RFLP method had a capability to detect as litter as 0.4 % of mutation, and revealed 16.3 % of thePIK3CA H1047R mutation in 86 CRC tissues, which was significantly higher than that discovered by DNA sequencing (9.3 %). A positive association between thePIK3CA H1047R mutation and the patients' age was first found, except for the negative relationship with the degree of tumor differentiation. In addition, the highly sensitive detection of a combinatorial mutation ofPIK3CA, KRAS andBRAF was achieved using individual PCR-RFLP methods. Conclusions We developed a sensitive, simple and rapid approach to detect the low-abundancePIK3CA H1047R mutation in real CRC specimens, providing an effective tool for guiding cancer targeted therapy.